A POLICY FRAMEWORK FOR SUSTAINABLE TOURISM DEVELOPMENT BASED ON PARTICIPATORY APPROACHES: A CASE STUDY IN THE KEDUNG OMBO TOURISM AREA-INDONESIA - Nafiah ARIYANI; Akhmad FAUZI (Geo Journal of Tourism and Geosites, 2022)
This research aims to find an alternative policy framework on tourism development Kedung Ombo-Indonesia. This study uses a qualitative approach by applying Multipol analysis method. Collecting data uses a focus group discussion method. The research participants are stakeholders of the area, such as local governments, reservoir managers, forest directors, and society. The result shows that an institutional development policy supported by good governance development programs is the best policy in the integrated scenario. Meanwhile, tourism development policies supported by developing public facilities, tourism convenience, tourism interest, marketing and promotion, and service quality are the best policy in the individual scenario.